2020
DOI: 10.1183/13993003.01808-2020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid onset honeycombing fibrosis in spontaneously breathing patient with COVID-19

Abstract: A 38-year-old man presented with a 6-day history of gradually worsening cough and asthenia and secondary anosmia and agueusia. He had no prior personal medical history. His mother had a history of diabetes mellitus and his son was followed for haemophilia A. His spouse had exhibited similar symptoms a week earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 3 publications
0
35
0
4
Order By: Relevance
“…At the time of this early follow-up, evolution toward lung fibrosis was suspected in 7 patients showing bronchial/bronchiolar dilatation within areas of ground-glass attenuation requiring further evaluation before assessing the presence of irreversible fibrotic changes. None of our patients had CT features of honeycombing as described during the acute phase of COVID-19 [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this early follow-up, evolution toward lung fibrosis was suspected in 7 patients showing bronchial/bronchiolar dilatation within areas of ground-glass attenuation requiring further evaluation before assessing the presence of irreversible fibrotic changes. None of our patients had CT features of honeycombing as described during the acute phase of COVID-19 [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Margot Combet and colleagues in an interesting case study published in European Respiratory Journal, reported rapid onset of honeycombing fibrosis in a patient with COVID-19 [ 6 ], with typical similarity to idiopathic pulmonary fibrosis (IPF) and similar questions were raised by Paolo Spagnolo et al regrading post-COVID-19 pulmonary fibrosis [ 7 ]. In histopathological micrographs from patients with IPF, we observed high ACE2 expression in the intimal, medial, and adventitial layers of the pulmonary arteries.…”
mentioning
confidence: 97%
“…This proves that these interstitial changes are not only a result of post-ARDS brosis or ventilator induced lung damage, but also a consequence of the direct virus induced injury and aberrant local immune response leading to ILD. Combet et al recently described a case of a spontaneously breathing patient who developed rapid honeycombing following COVID-19 disease which responded to high-dose steroids and nintedanib [26]. Tale et al also reported a similar case of a patient with persistent hypoxemia after recovery from moderate COVID-19 disease with 3 week follow-up HRCT showing artitechtural distortion, interlobar septal thickening and traction bronchiectasis [27].…”
Section: Discussionmentioning
confidence: 99%